The Effect of Implementing Good Corporate Governance on the Profitability and Financing Risk of Sharia Commercial Banks - Fenny Dewi Yuliani; Annisa Fithria (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The concept of good corporate governance (GCG) is based on agency theory which is expected to reduce conflicts of interest between agents and principals that can occur in every company, including sharia banks. This situation was realized by the Bank of Indonesia, which then issued a policy that emphasized the need for applying GCG in Bank Indonesia Regulation, namely PBI Number 11/33/PBI/2009. This study examines the effect of applying GCG on profitability and financing risk at the Sharia Commercial Bank in Indonesia. The application of GCG is measured using a composite value self-assessment GCG. Profitability is measured by the ratio of ROA and ROE, while the ratio of NPF measures financing risk. This study uses secondary data, namely annual and GCG implementation reports from 2010 to 2019, published on each official website of Sharia Commercial Bank. Based on the purposive sampling method, 8 of Sharia Commercial Bank ware sampled in this study with a total of 80 observations. Data analysis techniques use panel data regression analysis. The results showed that the application of GCG had a negative and significant effect on profitability measured by ROA and ROE ratios and had a significant positive effect on financing risk measured by the NPF ratio.